1998
DOI: 10.1111/j.1440-1827.1998.tb03954.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical overexpression of p16 protein associated with intact retinoblastoma protein expression in cervical cancer and cervical intraepithelial neoplasia

Abstract: Both p16 and retinoblastoma (Rb) proteins are important tumor suppressors that regulate the cell cycle. The status of both proteins in invasive cervical cancer and cervical intraepithelial neoplasia (CIN) has not yet been examined. The aim of this study was to investigate the expression of p16 and Rb proteins by immunohistochemistry using 98 formalin-fixed and paraffin-embedded samples of various cervical neoplastic lesions. Strong immunoreactivity for the p16 protein was observed in both the nuclei and cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
121
3
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 13 publications
19
121
3
3
Order By: Relevance
“…Our data confirm previous studies in HPV-transformed cells, cervical cancer cell lines and primary clinical lesions, 50,51,53,54,[61][62][63][64] suggesting that p16 INK4a is indeed overexpressed in cells transformed by HR-HPV types; thus evidence is provided against reports claiming reduced p16 INK4a expression in cervical lesions. 50 -52 In 14 of 32 CIN II lesions, 9 of 60 CIN III lesions and 5 of 60 cervical carcinoma samples, no HR-HPV infection could be identified despite strong and diffuse expression of p16 INK4a in the dysplastic cell layers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data confirm previous studies in HPV-transformed cells, cervical cancer cell lines and primary clinical lesions, 50,51,53,54,[61][62][63][64] suggesting that p16 INK4a is indeed overexpressed in cells transformed by HR-HPV types; thus evidence is provided against reports claiming reduced p16 INK4a expression in cervical lesions. 50 -52 In 14 of 32 CIN II lesions, 9 of 60 CIN III lesions and 5 of 60 cervical carcinoma samples, no HR-HPV infection could be identified despite strong and diffuse expression of p16 INK4a in the dysplastic cell layers.…”
Section: Discussionsupporting
confidence: 91%
“…However, some investigators reported a decreased expression of p16 INK4a in cervical cancer cells compared with normal cervical epithelia, 50 -52 whereas others observed the expected overexpression of p16 INK4a in HPV-transformed cells, cervical cancers and derived cell lines as well in preneoplastic precursor lesions. 53,54 In the present study, we therefore examined by immunohistochemistry using various monoclonal antibodies the p16 INK4a expression level in a large number of formalin-fixed, paraffin-embedded samples of normal cervical tissues, non-neoplastic and preneoplastic lesions and cervical carcinomas and their relationship to the status of HPV infection. No p16 INK4a immunoreactivity was seen in normal epithelia or hyperproliferative or inflammatory lesions without clearly morphologically proven dysplasia.…”
mentioning
confidence: 99%
“…[12][13][14] It may be inactivated by mutation or by promoter hypermethylation. In gynecologic specimens, p16 immunohistochemistry has been used as an indirect assay for HPV infection 1,15,16 and an even more indirect method of determining the primary site of origin [1][2][3] (in human papillomavirus (HPV)-associated cervical cancers, viral oncoproteins E6 and E7 bind activated RB with consequent upregulation of p16 and promotion of DNA synthesis 15,17 ). Well-recognized problems with this approach have been published; p16 expression has been described in non-neoplastic ciliated cells, the cells of tuboendometrioid metaplasia 16,18,19 and even in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, Sano et al clearly demonstrated the overexpression of p16 in CIN lesions and nearly all cervical carcinomas. 16,30 Moreover, because p16 overexpression is observed in many CIN lesions with highrisk and intermediate-risk HPV infections, p16 is be- lieved to be a suitable biomarker for screening CIN lesions and cervical carcinoma during routine pathologic diagnosis. Several studies using p16 have corroborated the above results and confirmed that nearly all high-grade CIN lesions and invasive carcinomas immunohistochemically express very high levels of p16, whereas normal and hyperplastic cervical epithelia usually do not express p16.…”
Section: Discussionmentioning
confidence: 99%